COMPARSION BETWEEN CBR PROTOCOL AND LEACH PROTOCOL USING NS2 AND TDMA - Manimekala, Ms.B. (IJRDO -Journal of Computer Science Engineering, 2016)
Technological advances in communications and computation have enabled the development of low-cost, low-power, small in size, and multifunctional sensor nodes in a wireless sensor network. Since the radio transmission and reception consumes a lot of energy, one of the important issues in wireless sensor network (WSN) is the inherent limited battery power within network sensor nodes. In addition to maximizing the lifespan of sensor nodes, it is preferable to distribute the energy dissipated throughout the wireless sensor network in order to maximize overall network performance. Packet loss that occurs due to mobility of the sensor nodes is one of main challenge in Wireless Sensor Network (WSN) and it comes in parallel with energy consumption. CBRP can change TDMA scheduling adaptively according to traffic and mobility characteristics. In this protocol the cluster head receive data from not only its member during the TDMA allocated time slot but also other sensor nodes that just enter the cluster when it has free timeslots, each cluster head takes turn to be the free cluster head in the network. The performance of proposed CBR protocol is evaluated using NS-2 and compared with LEACH protocol